2013
DOI: 10.1371/journal.pone.0072558
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Atorvastatin and Amlodipine Suppresses Angiotensin II-Induced Aortic Aneurysm Formation

Abstract: BackgroundAbdominal aortic aneurysm (AAA) is a life-threatening vascular disease. It is controversial whether statin and calcium channel blockers (CCBs) has an inhibitory effect on the expansion of AAA. Some studies reported that CCBs have an inhibitory effect on Rho-kinase activity. Rho-kinase plays an important role in the pathogenesis of various cardiovascular diseases. However, there is no study reporting of the association between Rho-kinase and human AAAs.Methods and ResultsExperimental AAA was induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Amlodipine was ineffective in preventing AAA in a rat model [13], and was further found to enhance elastin degradation in a pig model [15]. However, in other studies Amlodipine [7], or in combination with Atorvastatin [37], was found effective in preventing AAA in experimental mice. Several other CCBs, such as Diltiazem [8] and Azelnidipine [9], were also found to prevent AAA in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Amlodipine was ineffective in preventing AAA in a rat model [13], and was further found to enhance elastin degradation in a pig model [15]. However, in other studies Amlodipine [7], or in combination with Atorvastatin [37], was found effective in preventing AAA in experimental mice. Several other CCBs, such as Diltiazem [8] and Azelnidipine [9], were also found to prevent AAA in mice.…”
Section: Discussionmentioning
confidence: 99%
“…26 Thus, CyPA could be a novel therapeutic target for the treatment of aortic aneurysms. 20, 50 The role of CyPA as an essential protein for the development of AAA was highlighted in the New England Journal of Medicine. 49 blood pressure regulation.…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…Similarly, a therapy with amlodipine and atorvastatin suppressed MMP-2 activity in the aorta of mice infused with angiotensin II for a period of 28 days [65]. It has been suggested that amlodipine decreases MMP-2 expression through the protein tyrosin kinase pathway [66].…”
Section: Introductionmentioning
confidence: 99%